Determinan Kejadian Kanker Payudara pada Wanita Usia Subur (15-49 Tahun) - Ningrum, Megawati Puspa; Rahayu, RR. Sri Ratna (Indonesian Journal of Public Health and Nutrition, 2021)
Background: Breast cancer is a malignancy in breast tissue that can originate from the epithelium of the ducts and lobules. In Indonesia, the proportion of cancer cases in men and women is breast cancer, namely 19.18%. In women, breast cancer is the highest cancer case with a percentage of 34.30%. Methods: An observational analytic study with a cross sectional approach. The sample of this study was breast cancer patients in women of childbearing age in Indonesia using data from the 2016 Non-Communicable Disease Research. Data analysis used univariate analysis, bivariate analysis with Chi-Square test. Results: based on the results of multivariate analysis with logistic regression, there were 6 variables related to the incidence of breast cancer, namely age, family history of cancer exposure, menarche, parity, use of hormonal contraceptives and obesity.